SEED VIABILITY OF SOME COWPEA CULTIVARS AFFECTED BY SINGLE AND MIXED VIRUS INFECTIONS IN NIGER STATE, NIGERIA - Abdullahi, Ahmed A.; Galadima, Nura S.; Sani, Safiya (FUDMA JOURNAL OF SCIENCES, 2022)
A field trial was carried out in 2017 cropping season to assess the response of twenty five cultivars of cowpea to single and mixed infections with Blackeye cowpea mosaic virus (BICMV) and Cowpea mottle virus (CMeV) on seed quality. The field trial was conducted at the Teaching and Research Farm, Ahmadu Bello University, Zaria, Mokwa Station (090211 N and 50135 E, 201 m above sea level). The trial was a randomized complete block design replicated three times. Three cowpea seeds of each cultivar were sown after dressing with Apron – star at the rate of 3.0 kg seed per 10 g of the chemical. Seeds were sown at an intra and inter–row spacing of 0.30 × 0.75 m along the ridges and later thinned to two per stand at 2 weeks after sowing. Four independent trials were conducted simultaneously, for single and mixed infections. For the single virus infection, seedlings of the twenty five cultivars were inoculated at 10 days after sowing while for the mixed virus infections, seedlings were inoculated at 10 and 17 DAS. Seed viability was determined at the Crop Production Laboratory, Department of Crop Production, Federal University of Technology, Minna, Nigeria. The results of the experiment revealed that all cultivars were susceptible to single and mixed infections of the two viruses but to different extents. The viability of seeds from single infection with CMeV was slight in some instances, also, test of accelerated ageing for f
Keywords: Blackeye cowpea mosaic virus, Cowpea mottle virus, cowpea seeds, Germination; Longevity